(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті витлумачено основні поняття досліджуваної проблеми, проаналізовано зміст інтелектуальної культури учнів, окреслено основні шляхи її формування. Ключові слова: учні, інтелект, культура, інтелектуальна культура. In the article interpretation of the basic concept of the subject, analyzed the students intellectual culture, illustrates the key ways of its formation. Key words: students, intellect, culture, intellectual culture.